Preparation method of super-hydrophobic surface with underwater structure repair and gas production functions

By pre-stretching the shape memory composite material with gas production function, coating the metal film layer and near-infrared light heat treatment, the superhydrophobic micro-nano composite structure is formed, which solves the problem of poor surface superhydrophobic persistence in the underwater use environment, and achieves both underwater structure repair and gas production functions.

CN119590004APending Publication Date: 2025-03-11NORTHWEST INSTITUTE FOR NONFERROUS METAL RESEARCH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411767110.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing superhydrophobic surface has poor surface superhydrophobic persistence in underwater use environments and is prone to lose its superhydrophobicity due to mechanical external force damage.

Method used

The shape memory composite material with gas-producing function and intrinsically hydrophobic properties is pre-stretched and then coated with a metal film layer. The near-infrared light heat treatment is used to restore the material to its original state, forming a superhydrophobic micro-nano composite structure.

Benefits of technology

The underwater structure repair and gas production function of superhydrophobic surfaces is realized, and the dual recovery of surface micro-nano structure morphology and superhydrophobicity is promoted, ensuring the superhydrophobic properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119590004A_ABST
    Figure CN119590004A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a super-hydrophobic surface with underwater structure repairing and aerogenesis functions, which comprises the following steps: pre-stretching a shape memory composite material with aerogenesis function and intrinsic hydrophobicity, and then coating the shape memory composite material with a metal film layer; and then the shape memory composite material deformed through pre-stretching treatment is promoted to restore to the original state through near-infrared illumination, and the super-hydrophobic surface with underwater structure repairing and gas producing functions is obtained. Near-infrared light irradiation heat treatment is carried out after pre-stretching treatment, so that the shape memory composite material and the coated metal film layer retract and restore to the original state, a super-hydrophobic micro-nano composite structure is formed on the surface of the shape memory composite material and the coated metal film layer by utilizing the retraction difference of the shape memory composite material and the coated metal film layer, and the super-hydrophobic surface with underwater structure repairing and gas producing functions is obtained. And moreover, the preparation process is simple, the conditions are mild, special equipment is not needed, the cost is low, and the super-hydrophobic coating is suitable for the fields of corrosion prevention, icing prevention, pollution prevention, resistance reduction and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of super-hydrophobic surface preparation, and in particular to a method for preparing a super-hydrophobic surface having both underwater structure repair and gas production functions. Background Art

[0002] The super-hydrophobic surface micro-nano multi-level structure has excellent gas capture ability, which makes it have broad application prospects in many fields such as anti-corrosion, anti-icing, anti-fouling, drag reduction, etc. However, the biggest problem restricting the application of super-hydrophobic surface in actual industry is the poor super-hydrophobic durability of the material surface. The surface micro-nano multi-level structure is easily destroyed under the action of mechanical external force. At the same time, the air layer in the micro-nano multi-level structure will also disappear, and finally the material will permanently lose its super-hydrophobicity. In response to this problem, the main solution adopted in the current research work is to improve the mechanical stability of the super-hydrophobic surface micro-nano multi-level structure, which is mainly achieved by two methods: (1) by accurately designing the morphology of the micro-nano composite structure, using the micron-level structure with stable mechanical properties to protect the nanostructure, and finally playing the role of improving the stability of the micro-nano multi-level structure; (2) by constructing a micro-nano composite structure on the surface of a material with stable main mechanical properties (such as a hydrophobic elastomer, etc.), using the buffering effect of the elastomer material on the external force to enhance the stability of the micro-nano multi-level structure.

[0003] In addition, inspired by the self-repairing properties of the surface of organisms in nature, preparing a super-hydrophobic surface with a repair function by preparing a micro-nano multi-level structure is also an effective way to extend its service life. However, once the above-mentioned super-hydrophobic surface micro-nano multi-level structure is damaged underwater, water will penetrate into the gaps between the micro-nano multi-level structures. At this time, the air film will diffuse into the water and eventually disappear completely during the immersion process. Even if the surface morphology of the micro-nano multi-level structure can be restored, it will permanently lose its super-hydrophobicity. It can be seen that the preparation of a super-hydrophobic surface with underwater recovery function and active gas production function of a micro-nano multi-level structure is of great significance in practical applications. Shape memory materials have unique shape transformation characteristics and have been used to prepare super-hydrophobic surfaces with micro-nano structures and recovery functions. At present, only related research based on the shape memory effect to restore surface morphology and super-hydrophobicity has been reported. The maintenance of the surface super-hydrophobicity by the restoration of the micro-nano structure morphology alone is limited. A super-hydrophobic shape memory surface with both micro-nano structure morphology restoration and underwater gas production function has not yet been reported. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a method for preparing a super-hydrophobic surface with both underwater structure repair and gas production functions in view of the deficiencies of the above-mentioned prior art. The method pre-stretches a shape memory composite material with gas production function and intrinsic hydrophobicity, then coats it with a metal film layer, and then performs near-infrared light heat treatment to make it shrink back to its original state. By utilizing the shrinkage difference between the shape memory composite material and the metal film layer, a super-hydrophobic micro-nano composite structure is formed on its surface, thereby obtaining a super-hydrophobic surface with both underwater structure repair and gas production functions, promoting the dual recovery of the surface micro-nano structure morphology and super-hydrophobicity, and solving the problem of poor surface super-hydrophobic durability of the super-hydrophobic surface in an underwater use environment.

[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a super-hydrophobic surface with both underwater structure repair and gas production functions, characterized in that the method pre-stretches a shape memory composite material with gas production function and intrinsic hydrophobicity and then coats it with a metal film layer, and then promotes the shape memory composite material deformed by the pre-stretching treatment to recover to its original state through near-infrared light, thereby obtaining a super-hydrophobic surface with both underwater structure repair and gas production functions.

[0006] The above-mentioned method for preparing a super-hydrophobic surface having both underwater structure repair and gas production functions is characterized in that the method comprises the following steps:

[0007] Step 1: Blending epoxy shape memory resin, polydimethylsiloxane and gas generating material, stirring evenly to obtain a dispersion, and then placing the dispersion in a polytetrafluoroethylene mold for curing to obtain an intrinsically hydrophobic shape memory composite material film;

[0008] Step 2: pre-stretching the intrinsically hydrophobic shape memory composite material film obtained in step 1, and coating a metal film layer on the surface;

[0009] Step 3: Use near-infrared light to promote the shape memory composite material that has been deformed by pre-stretching treatment in step 2 and coated with a metal film layer to recover to its original state, thereby obtaining a super-hydrophobic surface with both underwater structure repair and gas production functions.

[0010] The above-mentioned method for preparing a super-hydrophobic surface with both underwater structure repair and gas production functions is characterized in that the volume ratio of the epoxy shape memory resin to polydimethylsiloxane in step one is 10:1 to 0.1.

[0011] The above-mentioned method for preparing a super-hydrophobic surface with both underwater structure repair and gas production functions is characterized in that the gas-producing material in step one is a mixed powder of sodium bicarbonate and citric acid in a mass ratio of 1:0.1 to 0.9, and the mass proportion of the gas-producing material in the dispersion is 0.01% to 10%.

[0012] The above-mentioned method for preparing a super-hydrophobic surface with both underwater structure repair and gas production functions is characterized in that the temperature of the curing treatment in step one is 60°C to 100°C, and the curing time is 60min to 150min; the thickness of the shape memory composite material film is 1mm to 3mm.

[0013] The above-mentioned method for preparing a super-hydrophobic surface with both underwater structure repair and gas production functions is characterized in that the aspect ratio of the shape memory composite material film pre-stretched in step 2 is greater than 3:1, the heating temperature of the pre-stretching treatment is 60°C to 80°C, the heating time is 3min to 10min, and the stretching ratio is 100% to 200%. The aspect ratio of the shape memory composite material film is controlled to be greater than 3:1 to facilitate the operation of the pre-stretching process; at the same time, the stretching process is performed while heating during the pre-stretching process.

[0014] The above-mentioned method for preparing a super-hydrophobic surface with both underwater structure repair and gas production functions is characterized in that the material of the metal film layer in step 2 is gold, silver, palladium, copper or platinum, and the time for coating the metal film layer is 60s to 120s. Generally, the material of the metal film layer can also be a metal other than gold, silver, palladium, copper or platinum that can form a film layer on the shape memory composite film.

[0015] The above-mentioned method for preparing a super-hydrophobic surface with both underwater structure repair and gas production functions is characterized in that the wavelength of the near-infrared light in step 3 is 800nm, the illumination time is 5s to 1min, the illumination distance is 10cm to 50cm, and the illumination power is 0.5W / cm 2 ~2W / cm 2 .

[0016] Compared with the prior art, the present invention has the following advantages:

[0017] 1. The present invention first pre-stretches a shape memory composite material with a gas-generating function and intrinsic hydrophobicity. Based on the shape memory effect, the stretched state of the material will be temporarily fixed, and then a metal film layer is coated. Then, the material is subjected to near-infrared light heat treatment, so that the deformed shape memory composite material after the pre-stretching treatment shrinks and recovers to its original state. The difference in shrinkage between the shape memory composite material and the metal film layer is used to form a super-hydrophobic micro-nano composite structure on its surface. When the super-hydrophobic micro-nano composite structure on the surface of the material in an underwater environment is damaged by mechanical external force, the near-infrared light irradiation can promote the repair of the microstructure morphology of the damaged area on the surface of the material, thereby obtaining a super-hydrophobic surface with underwater structure repair function, thereby ensuring the super-hydrophobic performance of the material.

[0018] 2. The present invention pre-incorporates a gas-generating material into a shape memory composite material to prepare a super-hydrophobic surface. When the super-hydrophobic micro-nano composite structure on the surface of the material in an underwater environment is damaged by an external mechanical force, the material spontaneously reacts with water at the damaged location to generate bubbles, thereby promoting the recovery of the surface air layer, improving the structural stability of the super-hydrophobic surface, and preventing the air layer from diffusing into the water and disappearing, thereby preventing the super-hydrophobic micro-nano composite structure from permanently losing its super-hydrophobicity, thereby ensuring the super-hydrophobic performance of the material.

[0019] 3. The preparation process of the present invention is simple, the conditions are mild, no special equipment is required, the cost is low, the technical effect is good, and it is suitable for practical application.

[0020] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The present invention is a schematic flow chart of a method for preparing a super-hydrophobic surface having both underwater structure repair and gas production functions.

[0022] Figure 2 This is a SEM image of the super-hydrophobic micro-nano composite structure formed on the surface of the shape memory composite material in Example 1 of the present invention.

[0023] Figure 3 This is a SEM image of the super-hydrophobic micro-nano composite structure formed on the surface of the shape memory composite material in Example 2 of the present invention.

[0024] Figure 4 This is a SEM image of the super-hydrophobic micro-nano composite structure formed on the surface of the shape memory composite material in Example 3 of the present invention.

[0025] Figure 5 This is a SEM image of the super-hydrophobic micro-nano composite structure formed on the surface of the shape memory composite material in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0026] Example 1

[0027] like Figure 1 As shown, this embodiment includes the following steps:

[0028] Step 1, blending an epoxy shape memory resin prepolymer and its curing agent polyetheramine, a polydimethylsiloxane prepolymer and its curing agent vinyl resin, and a gas-generating material, stirring the components evenly under mechanical action and removing bubbles to obtain a dispersion, and then introducing the dispersion into a polytetrafluoroethylene mold and curing treatment at 100°C for 60 minutes to obtain an intrinsically hydrophobic shape memory composite material film with a thickness of 3 mm; the molar ratio of the epoxy shape memory resin prepolymer and its curing agent polyetheramine is 5:2, the mass ratio of the polydimethylsiloxane prepolymer and its curing agent vinyl resin is 10:1, and the volume ratio of the epoxy shape memory resin prepolymer to the polydimethylsiloxane prepolymer is 10:0.1; the gas-generating material is a mixed powder of sodium bicarbonate and citric acid in a mass ratio of 1:0.1, and the mass proportion of the gas-generating material in the dispersion is 10%;

[0029] Step 2, the intrinsically hydrophobic shape memory composite material film with an aspect ratio of 5:1 obtained in step 1 is heated at 60°C for 10 minutes until the whole film is softened for pre-stretching treatment, and when the stretching ratio reaches 100%, the tension is maintained and the film is cooled to room temperature, and then placed in a gold spraying instrument for gold spraying treatment, with an applied voltage of 0.3 kV and an applied time of 100 seconds, and a gold film layer is coated on the surface;

[0030] Step 3: Use near-infrared light to irradiate the shape memory composite material that has been pre-stretched and deformed and coated with a gold film layer in step 2. The wavelength of the near-infrared light is 800nm, the irradiation time is 1min, the irradiation distance is 50cm, and the irradiation power is 2W / cm 2 , promoting the shape memory composite material that has been deformed by pre-stretching treatment and coated with a gold film layer to return to its original state. After being placed at room temperature for 24 hours, the surface becomes super-hydrophobic, and the contact angle of water droplets on the surface is 155°±2°, obtaining a super-hydrophobic surface with both underwater structural repair and gas production functions.

[0031] The material of the gold film layer in step 2 of this embodiment may also be replaced by silver, palladium, copper, platinum or other metals.

[0032] Figure 2 The SEM images of the super-hydrophobic micro-nano composite structure formed on the surface of the shape memory composite material in this embodiment, wherein (a) is a low-magnification image and (b) is a high-magnification image. Figure 2 It can be seen that a rich lamellar micro-nano wrinkled structure, namely a superhydrophobic micro-nano composite structure, is formed on the surface of the shape memory composite material.

[0033] Example 2

[0034] like Figure 1 As shown, this embodiment includes the following steps:

[0035] Step 1: Blend an epoxy shape memory resin prepolymer and its curing agent polyetheramine, a polydimethylsiloxane prepolymer and its curing agent vinyl resin, and a gas-generating material, stir the components evenly under mechanical action, remove bubbles to obtain a dispersion, and then introduce the dispersion into a polytetrafluoroethylene mold, and cure it at 100°C for 60 minutes to obtain an intrinsically hydrophobic shape memory composite material film with a thickness of 1 mm; the molar ratio of the epoxy shape memory resin prepolymer and its curing agent polyetheramine is 5:2, the mass ratio of the polydimethylsiloxane prepolymer and its curing agent vinyl resin is 10:1, and the volume ratio of the epoxy shape memory resin prepolymer to the polydimethylsiloxane prepolymer is 10:0.1; the gas-generating material is a mixed powder of sodium bicarbonate and citric acid in a mass ratio of 1:0.9, and the mass proportion of the gas-generating material in the dispersion is 0.01%;

[0036] Step 2, the intrinsically hydrophobic shape memory composite material film with an aspect ratio of 3:1 obtained in step 1 is heated at 80°C for 3 minutes until the whole film is softened for pre-stretching treatment, and when the stretching ratio reaches 200%, the tension is maintained and the film is cooled to room temperature, and then placed in a gold spraying instrument for gold spraying treatment, with an applied voltage of 0.3 kV and an applied time of 120 seconds, and a gold film layer is coated on the surface;

[0037] Step 3: Use near-infrared light to irradiate the shape memory composite material that has been pre-stretched and deformed and coated with a gold film layer in step 2. The wavelength of the near-infrared light is 800nm, the irradiation time is 5s, the irradiation distance is 10cm, and the irradiation power is 0.5W / cm 2 , promoting the shape memory composite material that has been deformed by pre-stretching treatment and coated with a gold film layer to return to its original state. After being placed at room temperature for 24 hours, the surface becomes super-hydrophobic, and the contact angle of water droplets on the surface is 157°±1.5°, obtaining a super-hydrophobic surface with both underwater structural repair and gas production functions.

[0038] The material of the gold film layer in step 2 of this embodiment may also be replaced by silver, palladium, copper, platinum or other metals.

[0039] Figure 3 The SEM images of the super-hydrophobic micro-nano composite structure formed on the surface of the shape memory composite material in this embodiment, wherein (a) is a low-magnification image and (b) is a high-magnification image. Figure 3 It can be seen that a rich lamellar micro-nano wrinkled structure, namely a superhydrophobic micro-nano composite structure, is formed on the surface of the shape memory composite material.

[0040] Example 3

[0041] like Figure 1 As shown, this embodiment includes the following steps:

[0042] Step 1: Blend an epoxy shape memory resin prepolymer and its curing agent polyetheramine, a polydimethylsiloxane prepolymer and its curing agent vinyl resin, and a gas-generating material, stir the components evenly under mechanical action, remove bubbles to obtain a dispersion, and then introduce the dispersion into a polytetrafluoroethylene mold, and cure it at 60°C for 150 minutes to obtain an intrinsically hydrophobic shape memory composite material film with a thickness of 2 mm; the molar ratio of the epoxy shape memory resin prepolymer and its curing agent polyetheramine is 5:2, the mass ratio of the polydimethylsiloxane prepolymer and its curing agent vinyl resin is 10:1, and the volume ratio of the epoxy shape memory resin prepolymer to the polydimethylsiloxane prepolymer is 10:0.5; the gas-generating material is a mixed powder of sodium bicarbonate and citric acid in a mass ratio of 1:0.7, and the mass proportion of the gas-generating material in the dispersion is 1%;

[0043] Step 2, the intrinsically hydrophobic shape memory composite material film with an aspect ratio of 4:1 obtained in step 1 is heated at 70°C for 5 minutes until the whole film is softened for pre-stretching treatment, and when the stretching ratio reaches 150%, the tension is maintained and the film is cooled to room temperature, and then placed in a gold spraying instrument for gold spraying treatment, with an applied voltage of 0.3 kV and an applied time of 60 seconds, and a gold film layer is coated on the surface;

[0044] Step 3: Use near-infrared light to irradiate the shape memory composite material that has been pre-stretched and deformed and coated with a gold film layer in step 2. The wavelength of the near-infrared light is 800nm, the irradiation time is 20s, the irradiation distance is 20cm, and the irradiation power is 1W / cm 2 , promoting the shape memory composite material that has been deformed by pre-stretching treatment and coated with a gold film layer to return to its original state. After being placed at room temperature for 24 hours, the surface becomes super-hydrophobic, and the contact angle of water droplets on the surface is 151°±2°, obtaining a super-hydrophobic surface with both underwater structural repair and gas production functions.

[0045] The material of the gold film layer in step 2 of this embodiment may also be replaced by silver, palladium, copper, platinum or other metals.

[0046] Figure 4 The SEM images of the super-hydrophobic micro-nano composite structure formed on the surface of the shape memory composite material in this embodiment, wherein (a) is a low-magnification image and (b) is a high-magnification image. Figure 4 It can be seen that a rich lamellar micro-nano wrinkled structure, namely a superhydrophobic micro-nano composite structure, is formed on the surface of the shape memory composite material.

[0047] Comparative Example 1

[0048] This comparative example comprises the following steps:

[0049] Step 1: Blend an epoxy shape memory resin prepolymer and its curing agent polyetheramine, a polydimethylsiloxane prepolymer and its curing agent vinyl resin, and a gas-generating material, stir the components evenly under mechanical action, remove bubbles to obtain a dispersion, and then introduce the dispersion into a polytetrafluoroethylene mold for curing at 100°C for 40 minutes to obtain an intrinsically hydrophobic shape memory composite material film with a thickness of 3 mm; the molar ratio of the epoxy shape memory resin prepolymer and its curing agent polyetheramine is 5:2, the mass ratio of the polydimethylsiloxane prepolymer and its curing agent vinyl resin is 10:1, and the volume ratio of the epoxy shape memory resin prepolymer to the polydimethylsiloxane prepolymer is 10:0.1; the gas-generating material is a mixed powder of sodium bicarbonate and citric acid in a mass ratio of 1:0.1, and the mass proportion of the gas-generating material in the dispersion is 10%;

[0050] Step 2, the intrinsically hydrophobic shape memory composite material film with an aspect ratio of 5:1 obtained in step 1 is heated at 60°C for 10 minutes until the whole film is softened for pre-stretching treatment, and when the stretching ratio reaches 50%, the tension is maintained and the film is cooled to room temperature, and then placed in a gold spraying instrument for gold spraying treatment, with an action voltage of 0.3 kV and an action time of 30 seconds, and a gold film layer is coated on the surface;

[0051] Step 3: Use near-infrared light to irradiate the shape memory composite material that has been pre-stretched and deformed and coated with a gold film layer in step 2. The wavelength of the near-infrared light is 800nm, the irradiation time is 1min, the irradiation distance is 50cm, and the irradiation power is 2W / cm 2 , promoting the shape memory composite material that was deformed by pre-stretching treatment and coated with a gold film layer to return to its original state. After being placed at room temperature for 24 hours, the surface became hydrophobic, and the contact angle of a water droplet on the surface was 103°, which could not achieve superhydrophobicity.

[0052] Figure 5 The SEM images of the hydrophobic micro-nano composite structure formed on the surface of the shape memory composite material in this comparative example, wherein (a) is a low-magnification image and (b) is a high-magnification image. Figure 5 It can be seen that the structure formed on the surface of the shape memory composite material is relatively flat and cannot reach a superhydrophobic state.

[0053] By comparing Examples 1 to 3 with Comparative Example 1, it can be seen that compared with the use of a shorter curing time when preparing the shape memory composite material film, a smaller stretching ratio during the pre-stretching treatment, and a shorter coating time when coating the gold film layer in Comparative Example 1, the present invention controls the curing time of the shape memory composite material film to ensure that a material with excellent shape memory effect is obtained, and controls the stretching ratio of the pre-stretching treatment and the time for coating the metal film layer to ensure that the shape memory composite material and the metal film layer have a suitable shrinkage difference, thereby forming a super-hydrophobic micro-nano composite structure on its surface that has both underwater structure repair and gas production functions.

[0054] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a super hydrophobic surface having both underwater structure repair and gas production functions, characterized in that: This method pre-stretches a shape memory composite material with gas production function and intrinsic hydrophobicity, then coats it with a metal film layer, and then promotes the deformation of the pre-stretched shape memory composite material to return to its original state through near-infrared light, thereby obtaining a super hydrophobic surface with both underwater structure repair and gas production functions.

2. The method for preparing a super-hydrophobic surface having both underwater structure repair and gas production functions according to claim 1, characterized in that: The method comprises the following steps: Step 1: Blending epoxy shape memory resin, polydimethylsiloxane and gas generating material, stirring evenly to obtain a dispersion, and then placing the dispersion in a polytetrafluoroethylene mold for curing to obtain an intrinsically hydrophobic shape memory composite material film; Step 2: pre-stretching the intrinsically hydrophobic shape memory composite material film obtained in step 1, and coating a metal film layer on the surface; Step 3: Use near-infrared light to promote the shape memory composite material that has been deformed by pre-stretching treatment in step 2 and coated with a metal film layer to recover to its original state, thereby obtaining a super-hydrophobic surface with both underwater structure repair and gas production functions.

3. The method for preparing a super-hydrophobic surface having both underwater structure repair and gas production functions according to claim 2, characterized in that: The volume ratio of the epoxy shape memory resin to polydimethylsiloxane in step 1 is 10:1 to 0.

1.

4. The method for preparing a super-hydrophobic surface having both underwater structure repair and gas production functions according to claim 2, characterized in that: The gas-generating material in step 1 is a mixed powder of sodium bicarbonate and citric acid in a mass ratio of 1:0.1-0.9, and the mass proportion of the gas-generating material in the dispersion is 0.01%-10%.

5. The method for preparing a super-hydrophobic surface having both underwater structure repair and gas production functions according to claim 2, characterized in that: The curing temperature in step 1 is 60° C. to 100° C., and the curing time is 60 min to 150 min. The thickness of the shape memory composite material film is 1 mm to 3 mm.

6. The method for preparing a super-hydrophobic surface having both underwater structure repair and gas production functions according to claim 2, characterized in that: The aspect ratio of the shape memory composite material film pre-stretched in step 2 is greater than 3:1, the heating temperature of the pre-stretching treatment is 60° C. to 80° C., the heating time is 3 min to 10 min, and the stretching ratio is 100% to 200%.

7. The method for preparing a super-hydrophobic surface having both underwater structure repair and gas production functions according to claim 2, characterized in that: The material of the metal film layer in step 2 is gold, silver, palladium, copper or platinum, and the time for coating the metal film layer is 60s to 120s.

8. The method for preparing a super-hydrophobic surface having both underwater structure repair and gas production functions according to claim 2, characterized in that: The wavelength of the near-infrared light in step 3 is 800nm, the illumination time is 5s to 1min, the illumination distance is 10cm to 50cm, and the illumination power is 0.5W / cm 2 ~2W / cm 2 .